Determination of the required sample size with assurance for Three Arm Non-Inferiority trials - Azmee Nor Afzalina, Mohamed Zulkifley, Ahmad Azhar, (N/A, 2013)
Determination of the required sample size with assurance for Three Arm Non-Inferiority trials by Azmee Nor Afzalina, Mohamed Zulkifley, Ahmad Azhar,